he assessment of the perinatal outcomes of the patients who underwent quad screening test - Kırlangıç, Mehmet Mete; Açmaz, Gökhan; Şahin, Erdem; Madendağ, Yusuf; Özdemir, Fatma; Müderris, İptisam İpek (Perinatal Medicine Foundation, 2020)
Objective The aim of this study is to assess the correlation between the poor perinatal outcomes and the serum biochemical markers such as maternal serum alpha fetoprotein (AFP), human chorionic gonadotropin (hCG), unconjugated estriol (uE3) and inhibin-A (INH-A) checked during the quad screening test. Methods In this retrospective study, the results of 485 pregnant women who underwent quad screening test in the Outpatient Clinic of Gynecology and Obstetrics of Faculty of Medicine at Erciyes University, Kayseri, Turkey between January 2018 and January 2019 and met the inclusion criteria were analyzed. The primary result of the study was established as the development of poor perinatal outcomes. The poor perinatal outcomes were defined as gestational diabetes (GDM), gestational hypertension (GHT), preeclampsia, intrauterine growth restriction (IUGR), preterm labor, premature rupture of membranes (PRM), oligohydramnios, polyhydramnios, HELLP syndrome, and intrahepatic cholestasis of pregnancy (ICP). Results A total of 485 pregnant women, who met the inclusion criteria, were included in the study. A significant correlation was found between AFP MoM≥2 and GHT, PRM, preterm labor, and the development of IUGR (p=0.017, p=0.033, p=0.037, and p=0.038, respectively). It was seen that the risk increased 5.1 times for GHT, 3.2 times for preterm labor, and 3.8 times for the development of IUGR. There was a significant correlation between hCG MoM≥2 and the risk of GHT development (p=0.024); however, the risk of GHT development increased for 3.8 times above this value. A significant correlation was found between INH-A being MoM≥2 and the development of GHT and HELLP syndrome (p=0.009 and p=0.005, respectively). In these pregnant women, the risk increased 31 times for the development of HELLP syndrome, and 9.4 times for GHT. In the cases with uE3 MoM£0.5, there was a significant correlation for the development of preeclampsia and HELLP syndrome (p=0.033 and p=0.049, respectively). On the other hand, there was no significant correlation between GDM, ICP, polyhydramnios, and oligohydramnios and AFP MoM, beta-hCG MoM, uE3 MoM and INH-A MoM values. Conclusion In our study, we found correlation between poor perinatal outcomes and the changes in AFP, hCG, uE3 and INH-A levels.